Elementary school guidance - Detjen, Ervin Winfred; Detjen, Mary Ford (New York : McGraw-Hill, 1952)
This book is written for all teachers-experienced, and prospective- who are interested in improving the mental health of children.
1. Studying the home environment of pupils -- 2. Understanding the physical needs of children -- 3. Discovering the social needs of children -- 4. Developing friendliness -- 5. Encouraging wise use of leisure time -- 6. Studying aggressive behavior -- 7. Handling angry feelings -- 8. Dealing with bullies -- 9. Attacking the problem of dishonesty -- 10. Controlling jealous feelings -- 11. Heeding the attention seeker -- 12. Understanding the shy, withdrawing child -- 13. Helping the daydreamer -- 14. Overcoming fears -- 15. Considering the cause of absence and tardiness -- 16. Developing responsibility -- 17. Encouraging fair play -- 18. Cultivating good manners -- 19. Improving family relationships -- 20. Creating wholesome pupil-teacher relations.
Includes bibliographical references and index.
Keywords: COUNSELING